2011
DOI: 10.1074/jbc.m110.153122
|View full text |Cite
|
Sign up to set email alerts
|

Docking-dependent Ubiquitination of the Interferon Regulatory Factor-1 Tumor Suppressor Protein by the Ubiquitin Ligase CHIP

Abstract: Characteristically for a regulatory protein, the IRF-1 tumor suppressor turns over rapidly with a half-life of between 20 -40 min. This allows IRF-1 to reach new steady state protein levels swiftly in response to changing environmental conditions. Whereas CHIP (C terminus of Hsc70-interacting protein), appears to chaperone IRF-1 in unstressed cells, formation of a stable IRF-1⅐CHIP complex is seen under specific stress conditions. Complex formation, in heat-or heavy metaltreated cells, is accompanied by a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 40 publications
(61 reference statements)
2
54
0
1
Order By: Relevance
“…We recently discovered that the E3-ubiquitin ligase CHIP binds to a site (amino acids 106 -140) within the major disordered domain of IRF-1 (Fig. 1C), facilitating ubiquitination of IRF-1 under specific stress conditions (33). Because disordered domains appear to favor multiple protein interactions, we speculated that the major disordered domain in IRF-1 may bind to other components of the IRF-1 regulatory network.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We recently discovered that the E3-ubiquitin ligase CHIP binds to a site (amino acids 106 -140) within the major disordered domain of IRF-1 (Fig. 1C), facilitating ubiquitination of IRF-1 under specific stress conditions (33). Because disordered domains appear to favor multiple protein interactions, we speculated that the major disordered domain in IRF-1 may bind to other components of the IRF-1 regulatory network.…”
Section: Resultsmentioning
confidence: 97%
“…2, A and B). These two peptides also contain the CHIPdocking site (33), suggesting that they may form a multiprotein binding interface on IRF-1. We have named this the Mf2 (multifunctional 2) domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These two protein-modification events can occur rapidly through dedicated enzymes, and often act cooperatively in mobilizing particular cellular pathways in response to extracellular signals (Ben-Neriah, 2002;Wang and Maldonado, 2006). For IRF1, under certain stress conditions, the C-terminus of Hsc70-interacting protein binds to and forms a stable complex with IRF1, allowing an increase in IRF1 ubiquitination and a decrease in IRF1 steady-state levels (Narayan et al, 2011). Following the removal of the C-terminal 70 amino acids from IRF1, which could be recognized by an E3 ligase, its degradation and polyubiquitination can be inhibited, suggesting that the C-terminal of IRF1 promotes ubiquitination.…”
mentioning
confidence: 99%
“…Importantly, further studies revealed that CHIP overexpression enhanced, whereas CHIP knockdown attenuated, TSA-mediated IRF-1 degradation. Although Narayan et al (41) reported that CHIP could bind IRF-1 directly, their data did not rule out the possibility that CHIP interacts with IRF-1 through HSP70. Because our data showed that TSA treatment enhanced the interaction between HSP70 and IRF-1 markedly (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…CHIP was identified as an E3 ligase for IRF-1 as well as a number of HSP70-associated proteins, such as ErbB2 and PTEN (47,48); however, it was reported that CHIP acted as the chaperone for IRF-1 in unstressed cells. Only under special conditions in which the interaction between CHIP and IRF-1 gets enhanced will CHIP target IRF-1 for ubiquitination and degradation (41). We therefore first determined the effect of TSA on the association between CHIP and IRF-1 by coimmunoprecipitation assays.…”
Section: Discussionmentioning
confidence: 99%